PENGARUH MARINASI EKSTRAK KULIT NENAS (Ananas Comocus L. Merr) PADA DAGING ITIK TEGAL BETINA AFKIR TERHADAP KUALITAS KEEMPUKAN DAN ORGANOLEPTIK - Muhammad Zulfahmi; Yoyok Budi Pramono; Antonius Hintono (Universitas Muhammadiyah Semarang, 2013)
This research aims to study the effect of pineapple peel extract marinate in Tegal’s duck meat second grade forward of tenderness and organoleptic properties. Design research used a completely randomized consisting of 4 treatments and 5 replications. Treatment is meat marinated in pineapple peel extract for 60 min with various concentrations are: 0% (distilled water), 5%, 10%, and 15%. The results showed marinated pineapple peel extract significantly affect for tenderness and organoleptic properties include color and flavor indicated on the p value <0.05, while the organoleptic properties of the texture are not significant, although the results showed the meat tends to be soft.